2015
DOI: 10.1186/s13046-015-0212-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated AKT1 is associated with poor prognosis in esophageal squamous cell carcinoma

Abstract: BackgroundThe epidermal growth factor receptor (EGFR) signaling pathway is important in regulating biological behaviors in many malignancies. We explored whether expression and activation of EGFR and several components on its downstream pathways have prognostic significance in patients with esophageal squamous cell carcinoma (ESCC).MethodsExpression of EGFR, phosphorylated (p)-EGFR, AKT1, p-AKT1, AKT2, p-AKT2, ERK1, ERK2, p-ERK1/2, STAT3, and p-STAT3 was assessed by immunohistochemical analysis of tissue micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 38 publications
(34 reference statements)
1
33
0
Order By: Relevance
“…To further explore the mechanisms underlying miR-495-mediated inhibition of ESCC cells ability, we examined whether miR-495 targeted Akt1. Akt1 is the crucial mediator of the PI3K/Akt signaling pathway and mediates various cellular functions in a number of tumor types, including gastric cancer [18], glioma [19], lung cancer [20], and ESCC [21]. In glioma patients, overexpression of Akt protein is correlated with later glioma grade and poor prognosis [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the mechanisms underlying miR-495-mediated inhibition of ESCC cells ability, we examined whether miR-495 targeted Akt1. Akt1 is the crucial mediator of the PI3K/Akt signaling pathway and mediates various cellular functions in a number of tumor types, including gastric cancer [18], glioma [19], lung cancer [20], and ESCC [21]. In glioma patients, overexpression of Akt protein is correlated with later glioma grade and poor prognosis [22, 23].…”
Section: Discussionmentioning
confidence: 99%
“…Also in our study, Biglycan mRNA fold expression and tissue Biglycan protein expression by IHC and western blotting in the tumour tissue were significantly higher than those in the adjacent normal tissue. Zhu et al 24 observed a twofold rise in the mRNA expression of biglycan in ESCC tissue as compared to their normal counterparts. This finding was also supported by showing a significantly higher immunostaining for Biglycan in ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…22 High expression of Biglycan in malignancy has been associated with poor prognosis as observed in endometrial cancer, oesophageal cancer and gastric cancer. [23][24][25] Knockdown of Biglycan using small interfering RNA (siRNA) in HCT116 colon cancer cell line inhibited cell proliferation and produced growth arrest. 26 As it also regulates the immune system, Biglycan has been found to be associated with auto-immune diseases like systemic lupus erythematosus (SLE) where it enhances the expression of CXCL13 which is a potent B cell chemo-attractant.…”
Section: Introductionmentioning
confidence: 99%
“…However, biglycan expression and serological levels of its processed byproducts correlate with the extent of liver fibrosis in murine models (108,204). Biglycan is also involved with progression and poor prognosis in a variety of malignancies such as gastrointestinal and endometrial cancers (7,122,221,377,415). In contrast, biglycan expression correlates with a favorable prognosis in bladder cancer where it seems to have an inhibitory effect on tumor cell proliferation (266).…”
Section: Proteoglycansmentioning
confidence: 99%